Cell-Penetrating Peptide Modified PEG-PLA Micelles for Efficient PTX Delivery - Qi Shuai (International Journal of Molecular Sciences, 2020)
On account of their excellent capacity to significantly improve the bioavailability and solubility of chemotherapy drugs, amphiphilic block copolymer-based micelles have been widely utilized for chemotherapy drug delivery. In order to further improve the antitumor ability and to also reduce undesired side effects of drugs, cell-penetrating peptides have been used to functionalize the surface of polymer micelles endowed with the ability to target tumor tissues. Herein, we first synthesized functional polyethylene glycol-polylactic acid (PEG-PLA) tethered with maleimide at the PEG section of the block polymer, which was further conjugated with a specific peptide, the transactivating transcriptional activator (TAT), with an approved capacity of aiding translocation across the plasma membrane. Then, TAT-conjugated, paclitaxel-loaded nanoparticles were self-assembled into stable nanoparticles with a favorable size of 20 nm, and displayed a significantly increased cytotoxicity, due to their enhanced accumulation via peptide-mediated cellular association in human breast cancer cells (MCF-7) in vitro. But when further used in vivo, TAT-NP-PTX showed an acceleration of the drug’s plasma clearance rate compared with NP-PTX, and therefore weakened its antitumor activities in the mice model, because of its positive charge, its elimination by the endoplasmic reticulum system more quickly, and its targeting effect on normal cells leading towards being more toxic. So further modification of TAT-NP-PTX to shield TAT peptide’s positive charges may be a hot topic to overcome the present dilemma.